2013
DOI: 10.1002/aic.14139
|View full text |Cite
|
Sign up to set email alerts
|

Analysis on development of magnetite hollow spheres through one‐pot solvothermal process

Abstract: in Wiley Online Library (wileyonlinelibrary.com) Monodisperse magnetite nanospheres with hollow interior structure were synthesized through one-pot solvothermal process, in an isothermal environment at 200 C for 12 h, using a sole iron precursor (FeCl 3 .6H 2 O) and without any template. We demonstrated the development of hollow structure of magnetite spheres by characterizing systematically the changes of morphology and crystal structure for different processing times. We also provided the cross-sectional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Furthermore, understanding of the formation mechanism is an essential prerequisite for establishing the scope of synthesis of Fe 3 O 4 spheres for broad applications. In previous studies [24][25][26][27][28][29][30][31][32], polyol has been widely employed as both solvent and reductant while either PAA or Na 3 Cit is used as stabilizer. Cheng et al [14] reported that the formation of Fe 3 O 4 spheres depended on the balance of surface tension and electrostatic repelling forces of citrate molecules on the surface of nanocrystals.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, understanding of the formation mechanism is an essential prerequisite for establishing the scope of synthesis of Fe 3 O 4 spheres for broad applications. In previous studies [24][25][26][27][28][29][30][31][32], polyol has been widely employed as both solvent and reductant while either PAA or Na 3 Cit is used as stabilizer. Cheng et al [14] reported that the formation of Fe 3 O 4 spheres depended on the balance of surface tension and electrostatic repelling forces of citrate molecules on the surface of nanocrystals.…”
Section: Introductionmentioning
confidence: 99%
“…This idea was further supported by Hagen et al's study, 51 in which Fe 3 O 4 nanocrystals were obtained by a thermal decomposition process of the mixed-valence binuclear iron complex. The preparation of nano Fe 3 O 4 using a solvothermal reduction route has been reported in many studies, 29,[66][67][68][69] where the following reactions existed in the system: Fe 3+ is reduced to Fe 2+ by a solvent, and Fe 3 O 4 is then formed through the association of Fe 3+ and Fe 2+ in an alkaline environment, with the following schematic equations for the relevant reactions:…”
mentioning
confidence: 99%
“…This idea was further supported by Hagen et al 's study, 51 in which Fe 3 O 4 nanocrystals were obtained by a thermal decomposition process of the mixed-valence binuclear iron complex. The preparation of nano Fe 3 O 4 using a solvothermal reduction route has been reported in many studies, 29,66–69 where the following reactions existed in the system: Fe 3+ is reduced to Fe 2+ by a solvent, and Fe 3 O 4 is then formed through the association of Fe 3+ and Fe 2+ in an alkaline environment, with the following schematic equations for the relevant reactions:Fe 3+ + 3OH − → Fe(OH) 3 → FeOOH→Fe 2 O 3 Fe(OH) 3 + Fe(OH) 2 → Fe 3 O 4 It has been demonstrated that, under elevated temperatures and alkaline conditions, the formation of Fe(OH) 3 and its subsequent conversion to FeOOH is a rapid reaction. 24,70 Furthermore, studies have shown that eqn (2) with a high activation energy is more difficult to conduct than eqn (1), 71–73 Therefore, in cases where the precursor did not contain Fe 2+ , FeOOH underwent further transformation into Fe 2 O 3 .…”
mentioning
confidence: 99%
“…In the past few years, MNPs gained great attention in the field of bioseparations due to their numerous advantages which include, but are not limited to, (i) reduced agglomeration [9]; (ii) large surface area resulting from their tremendous surface to volume ratios [10, 11]; (iii) ability to perform all relevant separation steps in one single container [12]; (iv) ease of manipulation by external magnetic field which accelerates the separation process [11, 13, 14]; and most importantly (vii) their versatile particle size ranging from few up to tens of nanometers, which hence makes it suitable for separating a wide range of biomolecules such as proteins (5-50 nm) and cells (10-100 nm) [15]. However, the nonprotected or bare nanoparticles could be prone to oxidation [16, 17].…”
Section: Magnetic Nanoparticles (Mnps)mentioning
confidence: 99%